Steering the Unsteerable? Aggregate Fiscal Stance and Spillover Effects in the Euro Area - Stephan Freitag; Jörg Stosberg (Intereconomics, 2018)
The concept of aggregate euro area fiscal stance and the underlying assumption of significantly positive cross-country fiscal spillovers is a highly debated topic. The European Commission seems intent on using this concept as a basis for introducing top-down coordination of European fiscal policies. This article argues that the spillover effects of fiscal impulses in one country to the rest of the euro area would be rather limited. Introducing fiscal top-down coordination would require a substantial shift of political competencies from member states to the European level. A discussion of potential changes to the current fiscal framework would need to be part of a wider debate on the future of the European Economic and Monetary Union.
Keywords: 330